2015
DOI: 10.1021/acs.chemmater.5b03579
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Catalysis of Pure-Silica and Heteroatom LTA

Abstract: Zeolite A (LTA) has many large-scale uses in separations and ion exchange applications. Because of the high aluminum content and lack of high-temperature stability, applications in catalysis, while highly desired, have been extremely limited. Herein, we report a robust method to prepare pure-silica, aluminosilicate (product Si/Al = 12–42), and titanosilicate LTA in fluoride media using a simple, imidazolium-based organic structure-directing agent. The aluminosilicate material is an active catalyst for the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 23 publications
2
83
0
1
Order By: Relevance
“…In addition to STW, numerous other phases were produced without significant variation in synthesis conditions, including LTA, RTH, IWV, CSV, as well as several phases that could not be identified or consisted of layered organosilicate materials. Synthesis of these microporous materials is not unexpected, because they have all been shown to be derived from similarly shaped imidazole-based OSDAs under crystallization conditions similar to those reported here (25)(26)(27)(28)32).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In addition to STW, numerous other phases were produced without significant variation in synthesis conditions, including LTA, RTH, IWV, CSV, as well as several phases that could not be identified or consisted of layered organosilicate materials. Synthesis of these microporous materials is not unexpected, because they have all been shown to be derived from similarly shaped imidazole-based OSDAs under crystallization conditions similar to those reported here (25)(26)(27)(28)32).…”
Section: Resultssupporting
confidence: 59%
“…This work demonstrated the feasibility of a priori predicting chemically synthesizable monoquaternary, imidazolium OSDAs to create a specified, fluoride-mediated, pure-silica framework. Additionally, STW has been reported to form using diquaternary imidazolium-based OSDAs that are of sufficient size to conform to 10MR channel structure, implying more rigid, chiral analogs may be included in the framework of STW, and may potentially impart structural chirality (24)(25)(26)(27)(28). Here, we implemented the previously published computational method implemented by Schmidt et al (24) and Pophale et al (29) and used the molecular design constraints suggested by Davis and Lobo (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Initial propane selectivities (time‐on‐stream=7–10 min) as a function of tetrahedral Si/Al for zeolite catalysts. The initial propane data points for SSZ‐17, RTH, LTA, Rho, SSZ‐13, and SSZ‐39 are from previous literature reports at the same reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9. Product selectivities of zeolitecatalysts compared to SAPO-34.The selectivity valuesa re obtained by averaging hydrocarbon selectivities for conversions of methanoli nthe range of 98-100%.S electivity data of SSZ-17 [7] (LEV),S SZ-39 [6] (AEI), SSZ-50 [31] (RTH), LTA, [32] and Rho [33] are from previous literature reports at the same reaction conditions. ChemPhysChem 2018, 19,412 -419 www.chemphyschem.org…”
Section: Resultsmentioning
confidence: 99%